Hämophilie-A-Therapie bei Erwachsenen - Siegmund, B.; Richter, H.; Pollmann, H. (Hämostaseologie, 2010)
In a retrospective study from a single treatment centre (Centre for Haemostaseology Muenster) the current treatment conditions of patients with severe haemophilia A (FVIII:C <1%) at the age of ≥ 16 years are described. Data were extracted from paper based diaries of patients in home treatment (n = 70). Results: A progressive preference towards prophylactic treatment compared to on demand therapy is observed. On average 2.4 injections per week (mean: 1750 IU FVIII per injection) are used in the prophylactic regimen. The consumption of FVIII concentrates is approximately fivefold increased compared to on demand therapy (average 0.5 injections per week). Meanwhile, recombinant FVIII concentrates have become widely accepted in all age groups, they show a proportion of 60% in the clinical practice of the study population.
Keywords: Haemophilia A; adults; treatment on demand; prophylaxis; factor VIII